Apolipoprotein B/A1 ratio as a potential marker of cardiovascular risk in women - Olufisayo Gabriel Ayoade (Wolters Kluwer Medknow Publications, 2021)
Background: There has been a significant steady rise in the prevalence of cardiovascular disease (CVD) among Nigerian women within the last decade. The balance between pro-atherogenic particles and antiatherogenic particles has been markedly reflected in the apolipoprotein B/A1 ratio (Apo B/A1), and this ratio has been shown to be the strongest single lipoprotein-related cardiovascular risk factor. The cutoff value for the apo B/A1 ratio that defines high cardiovascular risk has been proposed to be 0.8 for women. This study is to determine the apo B/A1 ratio in apparently healthy Nigerian women and to evaluate the relationship of this ratio with other lipid indices. Methods: A total of 161 apparently healthy female adults between the ages of 30 and 66 years were selected for this study over a period of 6 months. Plasma total cholesterols (TC), triglycerides (TG), and high-density lipoprotein cholesterol (HDL-C) were measured using the enzymatic methods, whereas low-density lipoprotein cholesterol (LDL-C) was calculated using the Friedewald formula. Apolipoprotein A1 and B were determined using immunoturbidimetry methods. Results: The mean of plasma apo B/A-I ratio in the studied participants was 0.68, with values ranging from 0.27 to 1.46. The percentage of participants with the apoB/apoA-I ratio exceeding 0.8 (the cutoff value for CVD risk) was 24.2%. The participants with apoB/apoA-I >0.8 were characterized by higher mean TC (216 mg/dl vs. 171 mg/dl; P < 0.001), TG (80 mg/dl vs. 66 mg/dl; P = 0.007), LDL-C (163 mg/dl vs. 120 mg/dl; P < 0.001), and lower HDL-C (36 mg/dl vs. 43 mg/dl; P < 0.001) compared with women with apoB/apoA-I < 0.8. Conclusion: This study has demonstrated that the women with apo B/A1 >0.8 have worse atherogenic lipid profile (high plasma TC, TG, low-density lipoprotein cholesterol, and low high-density cholesterol). It has also shown that only the apoB/A-I ratio correlates with other lipid markers; it should be considered as a potential useful tool in cardiovascular risk assessment in women. Its potential use in the national guideline for assessment and management of dyslipidemia will be invaluable.